Mobile Operator 4G Network Performance in Capital of East Kalimantan during the Covid19 Pandemic - Budiman, Edy (Jurnal Pekommas, 2021)
The 4th-Generation Long Term Evolution or 4G-LTE technology as data access and high-level wireless connections is an offer for internet service providers(ISPs) and competition in an effort to expand the network area in the mainland of Borneo. Although it continues to grow, however, in several urban areas in Kalimantan the cellular network is not evenly distributed. Further exploration studies are needed on the performance of the 4G-LTE network to optimize benefits and satisfy network users 4G LTE technology allows users to no longer be limited in space and become a solution to ensure connection continuity and data access speed. Service provider competition in an effort to increase its network coverage in Indonesia. Although it continues to improve, in practice. This study measures the quality of service experience (QOSE) the received signal power (RSRP/RSRQ) and noise ratio (SNR) on the 4G-LTE networks from three ISPs in the capital city of East Kalimantan Province. Measuring network signal quality using walk-test methods, Samarinda City Geographically It's a hilly and forested area. Measurement data analysis results of the 4G-LTE signals from the three ISPs have changed the RSRP, RSRQ, and SNR values. Some measuring points experienced a decrease in signal strength due to propagation loss factors such as the presence of dense and tall trees or buildings creating propagation to occur: spreading or diffraction and reflection. Another factor is the distance of the BTS or transmitter to the UE(user equipment) causing a weak signal received